A New Switch Correction Method for a Single-Receiver VNA - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter (Proceedings of the 43th European Microwave Week, 2013)
Single receiver vector network analyzers (VNA) are offering a cost efficient possibility to measure complex scattering parameters. One main drawback of this architecture is the larger required period of time to complete the measurement, due to the sequential capturing of the wave quantities. In order to reduce this handicap, a new switch correction scheme is detailed in this paper. The discussion includes a comparison to alternative methods based on measurements and simulations. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.anewsw

An Octave Bandwidth Finline Frequency Tripler - Hrobak, Michael; Sterns, M.; Stein, Wadim; Schramm, Marcus; Schmidt, Lorenz-Peter (6th German Microwave Conference, 2011)
In this paper a nearly octave bandwidth frequency tripler based on bilateral finlines is presented. The tripler covers the frequency range from 23 GHz to 40 GHz. The achieved conversion loss averages out at 17 dB. Design and test data of the tripler using antiparallel Schottky diodes are reported. A low cost, easy-to-handle Arlon AD1000 high frequency laminate substrate, processed by rapid prototyping laser decompositioning technique is used. The tripler design flow is based on cooperative-simulation using commercially available 3D fullwave and harmonic balance circuit solvers. A comparison of simulation results and measurement data is given. The impact of the ambiguity at defining the characteristic impedance of the hybrid finline on the simulation results is discussed.
lhft_intern.bib::Hrobak11

A Simplified Method for Measuring Complex S-Parameters Dedicated to Synthetic Instrumentation - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Lechner, A. (EUMW / EUMC, Paris, October, 2010)
The constantly emerging market for high and medium volume test applications in the area of high frequency devices calls for cost efficient test solutions. One way to achieve this is using modular reconfigurable measurement equipment, thus enabling the reuse of hardware. This tendency brought up some synthetic instruments capable of sophisticated high frequency measurements up to 6 GHz. One feature those COTS-(Commercial Off The Shelf) systems are lacking, is the ability to measure complex scattering parameters. This article introduces an architecture of a synthetic VNA (Vector Network Analyzer) that enables a cost efficient way of measuring S-Parameters. The theoretical basics, a simulation based accuracy estimation as well as first measurement results are presented as proof of concept.
lhft_intern.bib::Schramm10

Design and construction of an ultrawideband backward wave directional coupler - Hrobak, Michael; Sterns, M.; Seler, Ernst; Schramm, Marcus; Schmidt, Lorenz-Peter (IET Microwaves Antennas & Propagation, 2012)
In this study the design and construction of an ultrawideband backward wave directional coupler is presented. The symmetric, non-uniform coupler covers the frequency range from 2 to 50 GHz with an average coupling of 16.6 2.4 dB while establishing directivity values greater than 10 dB from 10 MHz to 33.8 GHz and 8 dB up to 48.4 GHz. The design is based on coupled microstrip lines suitable for integration into planar front end modules of modern measurement systems. To account for the dispersive behaviour of such waveguides, wiggly-line technique is utilised. Accurate extraction of the waveguide frequency-dependent distributed equivalent circuit parameters is done by 2D finite element electromagnetic field (EM) simulation. To balance out the remaining mistuning appropriate scaling parameters are introduced. The influence of common manufacturing and assembly tolerances on the device performance is analysed. Measurement results of the synthesised coupler with planar matched isolated port are presente
lhft_intern.bib::hrobakIetCoup

Design and Fabrication of Broadband Hybrid GaAs Schottky Diode Frequency Multipliers - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2013)
Frequency extender modules of vector network analyzers and signal generators, as well as front-end modules of semiconductor automatic test systems, make use of broadband resistive diode frequency multipliers. This paper presents the design and fabrication of innovative planar varistor frequency multipliers. Three frequency triplers (#1, #2, #3) and two frequency doublers (#4, #5), operating in the 60-110 GHz and 50-110 GHz frequency ranges, respectively, are designed. The hybrid architecture utilizes commercial gallium arsenide Schottky diodes from United Monolithic Semiconductors on thin-film processed high-permittivity alumina substrate. Synthesis is based on a co-simulation procedure between 3-D electromagnetic field and nonlinear harmonic balance circuit simulations. Scalar and spectral measurement data over the focused output frequency ranges are presented. Conversion loss values around 18 dB from 60 to 95 GHz and below 22 dB from 60 to 110 GHz are achieved with frequency tripler #1. Frequency doubler #5 achieves conversion loss values below 15 dB from 50 to 89 GHz and below 22 dB from 50 to 110 GHz. A comprehensive comparison of the presented work with reported frequency multipliers is included. © 2013 IEE
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEH.design
Keywords: 1.00-mm coaxial connector; Hybrid multiplier; Longitudinal E-field probe; Planar W -band multiplier; Schottky diode frequency multiplier; Varistor doubler; Varistor tripler

Impact of Different Post-Processing Methods on a One-Receiver 2-Port Synthetic VNA Architecture - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Konrad, M. (European Microwave Conference, Proceedings, 2011)
Production test of RF and electronic circuits is mainly driven by two restrictions, the initial investment in the equipment and the required measurement time, mostly describing the overall cost of test. This is one reason for the increased interest in synthetic instrumentation. The measurement of complex scattering parameters using synthetic instruments has been demonstrated. Improvement of the measurement accuracy and the speed while preserving a cost efficient solution is the focus of this contribution. Comparing the hardware demands using different calibration and post-processing steps gives an insight into a cost efficient design of a synthetic Vector Network Analyzer (sVNA).
lhft_intern.bib::Schramm11a

Measurement Setup for Non-Destructive Complex Permittivity Determination of Solid Materials Using Two Coupled Coaxial Probes - Cenanovic, Amir; Schramm, Marcus; Schmidt, Lorenz-Peter (IMS 2011, 2011)
A non-destructive microwave measurement setup for broadband complex permittivity determination of solid materials over a frequency band from 0.05 GHz to 6 GHz is presented. The setup design was optimized for measurements of glass materials with planar and convex surfaces, but works with other dielectric materials as well. The measurement method is based on the near field coupling of two open-ended coaxial probes through the material under test (MUT). A theoretical modeling of this measurement configuration was performed, using a 3D full-wave electromagnetic field simulator. Two identical coaxial probes and an equivalent calibration kit, in order to perform a TRL calibration of the proposed setup, were designed. The calibration procedure of the measurement setup is explained and experimental results are presented.
lhft_intern.bib::Cenanovic11a

MOS-16: A New Method for In-Fixture Calibration and Fixture Characterization - Schramm, Marcus; Schür, Jan; Hrobak, Michael; Schmidt, Lorenz-Peter; Konrad, Michael (ARFTG, 2011)
lhft_intern.bib::Schramm11

Optimized method for achieving accurate signals for “True-Mode” S-parameter measurements - Schramm, Marcus; Hrobak, Michael; Schür, Jan; Schmidt, Lorenz-Peter; Konrad, Michael (45^th European Microwave Conference, 2015)
Due to the capabilities of modern vector network analyzers (VNAs), the usage of “True-Mode”-signals for characterizing and testing active differential devices is quite convenient. Nevertheless in cases, in which the device under test (DUT) and/or the measurement setup introduces a coupling between the required stimulus signals, current methods require some iteration time to achieve the desired phase and amplitude settings. In this paper a new approach will be introduced, which leads to an optimized testing time which can be crucial especially in industrial production tes
lhft_intern.bib::Schramm2015

Planar D-Band Frequency Doubler and Y-Band Tripler on PTFE Laminates - Hrobak, Michael; Sterns, M.; Schramm, Marcus; Stein, Wadim; Poprawa, F.; Ziroff, A.; Schür, Jan; Schmidt, Lorenz-Peter (Proceedings of the 38th International Conference on Infrared, Millimeter and Terahertz Waves IRMMW-THz 2013, 2013)
To extend the frequency range of existing short-range radar modules for industrial applications, millimeter-wave frequency multipliers based on cost-effective PCB technology are required. This paper describes a zero-bias D-band frequency doubler and Y-band frequency tripler based on pure PTFE material and the commercially available DBES105a diode from United Monolithic Semiconductors (UMS). At an input drive level range of 16 dBm to 18 dBm the multipliers deliver output power levels POUT ∈ [5, -5] dBm from 100 GHz to 160 GHz and POUT ∈ [-11, -20] dBm from 180 GHz to 230 GHz. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar

Planar Varistor Mode Schottky Diode Frequency Tripler Covering 60 GHz to 110 GHz - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (Proceedings of the International Microwave Symposium 2013, 2013)
Frequency extender modules of vector network analyzers (VNA) and signal generators, as well as front end modules of semiconductor automatic testsystems (ATS) make use of broadband resistive diode frequency multipliers. We present the design and construction of a planar varistor tripler utilizing commercial gallium arsenide (GaAs) Schottky diodes on thin-film processed alumina (Al 2O3) substrate. Synthesis is based on a co-simulation procedure between 3D electromagnetic field (EM) and nonlinear circuit simulations. Measurement data over the focused output frequency range from 60 GHz to 110 GHz is presented. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar_1
Keywords: 1 mm coaxial connector; Planar W-band multiplier; Schottky diode frequency multiplier; Varistor tripler

Planar Zero Bias Schottky Diode Detector Operating in the E- and W-Band - Hrobak, Michael; Sterns, Michael; Schramm, Marcus; Stein, Wadim; Schmidt, Lorenz-Peter (Proceedings of the 43th European Microwave Week, 2013)
Schottky diode detectors are the method of choice for many scalar power measurement applications in the millimeter wave frequency range. Power monitoring of forward and backward travelling waves is especially important within signal generator frequency extension modules and front end modules of semiconductor automatic test systems (ATS). We present the synthesis and characterisation of a planar zero bias Schottky diode (ZBD) detector that covers an input frequency range of 60 GHz to 110 GHz. The planar design is based on thin-film processed Al2O3 substrate. The utilized gallium arsenide (GaAs) diodes are commercially available from Virginia Diodes, Inc. (VDI). The presented measurement data is compared to results from 3D electromagnetic field (EM) and nonlinear circuit simulations. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.planar_5
Keywords: W-Band DC Block; W-Band Detector; W-Band RF Choke; Zero Bias Schottky Diode

Virtuelle Instrumente in der Praxis - Hrobak, Michael; Schramm, Marcus; Schmidt, Lorenz-Peter; Lechner, Armin (Virtuelle Instrumente in der Praxis, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.LEH.virtue